Preoperative Urine Culture Results Correlate Poorly with Bacteriology of Urologic Prosthetic Device Infections. Issue 1 (1st January 2017) - Kavoussi, Nicholas L.; Siegel, Jordan A.; Viers, Boyd R.; Pagliara, Travis J.; Hofer, Matthias D.; Cordon, Billy H.; Shakir, Nabeel; Scott, Jeremy M.; Morey, Allen F.
Abstract: Introduction: Although preoperative negative urine culture results and treatment of urinary tract infections are generally advised before artificial urinary sphincter (AUS) and penile prosthesis (PP) surgery to prevent device infection, limited evidence exists to support this practice. Aim: To evaluate the relation between preoperative urine culture results and the bacteriology of prosthetic device infections. Methods: Men undergoing AUS and/or PP placement at a tertiary referral center from 2007 through 2015 were analyzed. A total of 713 devices were implanted in 681 patients (337 AUSs in 314 patients and 376 PPs in 367 patients), of whom 259 (36%) did not have preoperative urine culture and were excluded. The remaining 454 patients received standard broad-spectrum perioperative antibiotics. Two patient groups were identified based on preoperative urine cultures: group 1 had negative urine culture results and group 2 had untreated asymptomatic positive urine culture results identified postoperatively. Main Outcome Measures: Device infection was diagnosed clinically and cultures obtained from the explanted device and tissue spaces were compared with preoperative urine culture results. Results: Although multivariate analysis showed that patients undergoing AUS placement had a 4.5-fold greater risk of positive urine culture results (114 of 250, 45%) compared with those undergoing PP placement (36 of 204, 18%; P < .001), infection rates between device types were similar (8 of 250 for AUSs [3%] and 7 of 204 for PPs [3%]; P = .89). At a median follow-up of 15 months, device infection occurred in 15 of 454 devices (3%) implanted and no differences in infection rates were noted between urine culture groups (10 of 337 in group 1 [3.3%] and 5 of 117 in group 2 [4.3%]; P = .28). Remarkably, only 1 of 15 device infections (7%) had the same organism present at preoperative urine culture. Conclusions: Despite the finding that patients with AUS placement had a 4.5 times higher rate of positive urine culture results than patients with PP placement, preoperative urine culture results appeared to show little correlation with the bacteriology of prosthetic device infections.